Unusual case presentations associated with the CD45 C77G polymorphism - Tchilian, E; Gil, J; Navarro, M; Fernandez-Cruz, E; Chapel, H; Misbah, S; Ferry, B; Renz, H; Schwinzer, R; Beverley, P (2006)
CD45, the leucocyte common antigen, is a haematopoietic cell specific tyrosine phosphatase. Human polymorphic CD45 variants are associated with autoimmune and infectious diseases and alter the phenotype and function of lymphocytes, establishing CD45 as an important regulator of immune function. Here we report four patients with diverse diseases with unusual clinical features. All four have the C77G polymorphism of CD45 exon 4, which alters the splicing and CD45RA/CD45R0 phenotype of lymphocytes. We suggest that C77G may be a contributing factor in these unusual cases. © 2006 British Society for Immunology.